The Problems of Interpretation and Reflection of Equity in the Financial Statements of the Organization - E. S. ruzhilovskaya; T. Yu. Druzhilovskaya (Учёт. Анализ. Аудит)
Equity is the most important object of accounting and an integral element of the financial statements and accounting reports of any organization. At the same time, our research indicates that today there are significant problems in the field of interpretation and reflection of the equity of modern organizations in accounting reports, which are typical for both the theory and practice of accounting and reporting, as well as for regulatory documents and scientific literature. These problems have been identified by the authors both in the theory and practice of accounting and reporting, both in regulatory documents and in the scientific literature. This article is devoted to the analysis of these problems and ways to solve them. Research methods included analysis, synthesis, grouping and analogy methods, comparison, systemic and logical approaches. In the course of the study, the scientific literature and Russian and International Standards relating to the interpretation, accounting and reflection in the financial statements of the equity of organizations were critically analyzed. As a result, proposals were developed and substantiated for solving the identified problems in the above areas. The results of this study can be useful to a wide range of readers interested in the problems of modern accounting and reporting, can be applied in the practical work of the accounting departments of organizations, in the educational process of higher educational institutions and in the development and improvement of relevant regulatory documents on accounting.